2001
DOI: 10.1111/j.1469-7793.2001.0273l.x
|View full text |Cite
|
Sign up to set email alerts
|

Origin and propagation of spontaneous excitation in smooth muscle of the guinea‐pig urinary bladder

Abstract: The origin and propagation of waves of spontaneous excitation in bundles of smooth muscle of the guinea‐pig bladder were examined using intracellular recording techniques and visualization of the changes in the intracellular calcium concentration ([Ca2+]i). Bladder smooth muscle cells exhibited spontaneous transient increases in [Ca2+]i which originated along a boundary of each smooth muscle bundle and then spread to the other boundary with a conduction velocity of 2.0 mm s−1. Spontaneous increases in [Ca2+]i … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
118
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(131 citation statements)
references
References 24 publications
12
118
1
Order By: Relevance
“…These effects were associated with membrane depolarization and an increase in contractile activity. These results are consistent with previous observations in GBSM cells (24,29) and other visceral smooth muscle cells (9,42). The time-dependent decreases of these events caused by prolonged exposure (not significant) are similar to the observations on slow waves in the small intestine (4,19); however, unlike in the gallbladder, SERCA pump inhibitors did not cause a transient augmentation of slow wave action potential in the small intestine (17) and inhibited slow waves and spontaneous transient depolarizations in the guinea pig gastric pylorus (36,37).…”
Section: Discussionsupporting
confidence: 94%
“…These effects were associated with membrane depolarization and an increase in contractile activity. These results are consistent with previous observations in GBSM cells (24,29) and other visceral smooth muscle cells (9,42). The time-dependent decreases of these events caused by prolonged exposure (not significant) are similar to the observations on slow waves in the small intestine (4,19); however, unlike in the gallbladder, SERCA pump inhibitors did not cause a transient augmentation of slow wave action potential in the small intestine (17) and inhibited slow waves and spontaneous transient depolarizations in the guinea pig gastric pylorus (36,37).…”
Section: Discussionsupporting
confidence: 94%
“…This observation is a clear indication of the presence and potential physiological relevance of the intercellular pathway. Consistent with these data, intercellular diffusion of hydrophilic dyes (i.e., Lucifer yellow) also has been observed between detrusor myocytes in situ, and gap junction-mediated intercellular calcium waves have been documented among detrusor myocytes in culture (37,38) and in situ (27,28). Furthermore, electron microscopy, immunogold labeling, confocal immunofluorescence, and Western blot techniques have all confirmed the presence of small junctional plaques composed of Cx43, and also Cx45, between human detrusor myocytes (25,32,36,37).…”
supporting
confidence: 68%
“…4, these propagations are by no means secure and may easily break down into smaller components, reverting back to microscopic propagation in one or a few bundles. We don't know what induces these spontaneous electrical collaborations involving many bundles, but it may be interesting to note that the interstitial cells that have been shown to occur in the wall of the bladder appear to be preferentially located along the edges of the bundles (6,25,26,37). If there were a possibility of signaling between adjacent bundles, for example through paracrine pathways, then electrical propagation across more bundles might then be promoted.…”
Section: Domementioning
confidence: 99%
“…Hashitani et al (25) have meticulously studied the propagation of action potentials and of calcium waves along layers of bundles isolated from the guinea pig bladder and have shown that the electrical length constants were much higher in the longitudinal or axial direction compared with the transverse direction (425 vs. 12.5 m, respectively). In addition, neurobiotin injected into one cell would readily spread to neighboring cells located in the axial direction but not to those located in the transverse direction (25). Recording from two microelectrodes simultaneously, in pig and human bladder, revealed a similar anisotropy with the major axis in the longitudinal direction (24).…”
Section: Domementioning
confidence: 99%